Analisis Transformasi Digital dalam Pembiayaan Syariah (Studi Kasus BSI KCP Payakumbuh) - Selma Andriyanti; Septria Susanti (ARZUSIN, 2026)
Although digital transformation in Islamic banking has received attention in various studies, research that specifically discusses its impact on the accessibility of sharia financing in a local context remains limited. This study aims to analyze the impact of digital transformation on the accessibility of sharia financing and to identify the obstacles to its implementation at BSI KCP Payakumbuh. This study used a qualitative approach with a case study design, involving a number of informants consisting of employees and customers selected through purposive sampling. Data were collected through semi-structured interviews, observation, and documentation, and were then analyzed using thematic analysis techniques through the stages of data reduction, data display, and conclusion drawing. The results showed that digital transformation facilitated service access, increased the speed and efficiency of the financing process, and strengthened information transparency for customers. However, its implementation still faced obstacles in the form of limited digital literacy and internet network access among some customers. These findings contribute to the development of studies on digital transformation in the context of Islamic banking and expand understanding of the implementation of financing service digitalization. This study concludes that optimizing digital services requires technological and human resource readiness, as well as strengthening digital literacy and technological infrastructure so that the accessibility of sharia financing can be improved more effectively.